1999
DOI: 10.1080/10903129908958943
|View full text |Cite
|
Sign up to set email alerts
|

Blood loss estimation by out-of-hospital emergency care providers

Abstract: Prehospital care providers are not accurate at estimating spilled blood volumes. This ability can be improved with limited education. Slides appear to be as effective as viewing actual spill sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 2 publications
3
17
0
Order By: Relevance
“…The large range of answers seen suggests that physicians are imprecise in addition to being inaccurate. This is consistent with prior studies that have examined other specialties' estimates of blood loss in a variety of scenarios, including active patient blood loss, 13, 6 blood spilled on the ground, 5 blood spilled onto drapes and sponges, 4 blood placed in a commode, 8 and blood loss estimated at the scene of trauma. 7 …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The large range of answers seen suggests that physicians are imprecise in addition to being inaccurate. This is consistent with prior studies that have examined other specialties' estimates of blood loss in a variety of scenarios, including active patient blood loss, 13, 6 blood spilled on the ground, 5 blood spilled onto drapes and sponges, 4 blood placed in a commode, 8 and blood loss estimated at the scene of trauma. 7 …”
Section: Discussionsupporting
confidence: 87%
“…Prior studies have suggested that health professionals tend to overestimate small losses (<150 mL) and underestimate large ones (>150 mL). 3,58 Our study found similar results. Comparing the larger blood loss on the bed sheet scenario (500 mL) to the smaller blood loss in the T-shirt scenario (100 mL), there were considerably more underestimates with the larger loss.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In a study using paramedics as subjects it was found that estimations of spilled blood volumes were not accurate, but that after limited training with the repeated viewing of actual spilled volumes or of slides of similar spilled volumes, the ability to estimate the volume of spilt blood was significantly improved 3 …”
Section: Discussionmentioning
confidence: 99%